Cutaneous Leishmaniasis in an American Adolescent Returning From Israel. (6th June 2018) - Ganjaei, Kimia G; Lawton, Kira; Gaur, Sunanda
Abstract: We present here the case of a healthy 16-year-old American girl who returned from an organized trip to Israel with cutaneous leishmaniasis caused by Leishmania major ; the infection was treated successfully with paromomycin-gentamicin ointment. She was initially misdiagnosed with staphylococcal and pseudomonal cellulitis. Although cutaneous leishmaniasis is seen only rarely in the United States, it should be considered when diagnosing new skin lesions after travel to affected countries.